Organ donation in the Covid-19 pandemic: perception of professionals in carrying out the family interview (Research, Society and Development, 2022)
This research aimed to learn about the perception of health professionals about carrying out the family interview for the donation of organs and tissues for transplantation during the pandemic. This is a qualitative, descriptive, exploratory study carried out from July to August 2022, with 08 nurses from different hospitals in the city of Maringá. The material was collected through a recorded interview, with the guiding question “Tell me how it was for you to carry out the family interview for organ and tissue donation in the face of the pandemic”. The narratives were submitted to Bardin's content analysis technique. Four categories emerged: “Motivations of professionals in carrying out the family interview for organ and tissue donation for transplantation in the face of the Covid-19 pandemic”; “Difficulties for carrying out the family interview in the face of Covid-19”; “Facilitators for carrying out the family interview through Covid-19”; “Perception of professionals on carrying out the family interview in the pandemic in the context of the pandemic”. The study is expected to contribute to teaching and assistance practices in this specialty, encouraging Health Promotion, fostering the creation of Public Policies, investment, training and permanent monitoring of these professionals.